Critical Pedagogy and Critical Interculturality - Itxaso García Chapinal (PraxisForschungLehrer*innenBildung, 2022)
Diversity in the classroom among students or regarding knowledge is often perceived as being a source of conflicts and tensions. However, diverse knowledge and experiences should be addressed at school as being part of a process of empowerment and as supporting democratic values at school, both among students and teachers. Critical pedagogy and critical interculturality try to provide theoretical tools for this purpose.